Mismatch losses mitigation of PV-TEG hybrid system via improved RIME algorithm: Design and hardware validation - Yang, Bo; Wang, Jiarong; Su, Shi; Li, Yulin; Wu, Pengyu; Yang, Zhaowei; Fan, Heng; Li, Wenting; Li, Jiale (Journal of cleaner production, 2024)
The heat dissipated during the working process of the photovoltaic (PV) system may cause the working temperature to be too high, which will affect the power generation efficiency of the system. To make full use of solar energy and maintain suitable operating temperature, this article designs an array model of stacked photovoltaic-thermoelectric generation (PV-TEG) hybrid power generation system. Meanwhile, considering that partial shielding conditions (PSC) may lead to component mismatch, power reduction and so on, this paper proposes a PV-TEG hybrid system reconfiguration method based on the improved RIME (IRIME) algorithm. Firstly, according to the irradiance data on the PV modules, the IRIME algorithm is used to obtain the optimal electrical connection scheme. Then, according to the optimal scheme, the electrical connection of the hybrid system is reconfigured to achieve the purpose of suppressing the multi-peak phenomenon in the generation process and increasing the power generation. To verify the feasibility of the IRIME algorithm, ten PSCs are simulated on two PV-TEG hybrid systems of different scales to carry out simulation experiments. The simulation results show that the average output power of the hybrid system in both 6 × 6 and 6 × 10 scales has been improved by 26.76% and 30.47% after reconfiguration, respectively. Meanwhile, to further test the performance of this method, this article used PSO, GA, ACO, BWO, GWO, ALO and RIME for comparative experiments. The experimental results showed that the IRIME algorithm has better universality in the reconfiguration problem of hybrid systems. In addition, this article utilized the RTLAB platform to conduct hardware in the loop (HIL) experiments on the proposed reconfiguration method, which further verified the hardware feasibility of the method.